Cervical Cancer Screening and Chinese Women: Insights from Focus Groups - Chang, Sabrina C.; Woo, Jane S.; Yau, Vickie; Gorzalka, Boris B.; Brotto, Lori A. (Frontiers in Psychology, 2013)
Objective: Despite extensive efforts to raise awareness, Papanicolaou (Pap) testing rates among Chinese women living in North America remain low compared with Euro-American women. Although the lower Pap testing rate and ensuing health repercussions among Chinese women are well characterized, mechanisms underlying such health disparities are not. The aim of this study was to use a qualitative approach to delineate such mechanisms. Qualitative approaches to understand constructs within the domain of sexual and reproductive health have been shown to be particularly appropriate, and offer a nuanced view of sexuality that is not afforded by traditional quantitative methods. Method: We carried out two focus groups aimed at exploring how Mandarin-speaking and English-speaking Chinese women experience Pap testing (N = 12). The women were invited to partake in the focus groups from having participated in a large-scale quantitative study. Participants were all first-generation immigrants and their average age was 53-years-old. We used content analyses to analyze transcripts and extract themes. Results and Discussion: The women heavily endorsed traditional Chinese medicine philosophy, conceptualizing physical health holistically, and valuing preventative measures over screening and interceptive measures. Pap testing was described as qualitatively different from other screening procedures, such that women assigned a sexually charged meaning to Pap testing, often discussing it in relation to sexual activity and promiscuity. Women expressed their preference for the compulsory and depersonalized manner that Pap tests are performed in their home country of China, as this lessens the embarrassment associated with undergoing Pap testing. Conclusion: Three mechanisms may contribute to lower Pap testing among middle-aged first-generation Chinese immigrants: preference for Chinese medicine philosophy, perceived sexualization of Pap testing, and the institutionalization of medical care. Implications for improving the reproductive health of Chinese women are discussed.